Robotics and STEM education in Portugal - Costa, Manuel F. M. (2020)
Over 20 years ago the robotics, industrial automation and artificial intelligence research groups of the Portuguese universities began a number of initiatives and activities in order to bring these subjects into the Portuguese high schools. A large number of lectures and demonstration activities were promoted. Robotics completions had a major positive effect. Initially focused on K12 students soon the activities were extended to all school levels with the combined efforts of the research groups involved in the ROBOCUP competitions, the National Ciência Viva Agency and Hands-on Science Network, as well as many schools and professional schools. The World Robotics Competition, ROBOCUP2004 on the Spring of 2004 in Lisbon was a key moment to the development educational robotics and artificial intelligence in STEM education in Portugal. A short overview of this evolutionary process will be given in this presentation.